1943
DOI: 10.1104/pp.18.1.114
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ion Exchange Materials in Studies on Corn Nutrition

Abstract: (7), who have studied artificial zeolites and the clay fraction from the soil and used them as a source of ions for plants. ALBRECHT and MCCALLA (1) give a very good account of this subject and references to previous work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1946
1946
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…6. Plants dependent upon magnesium, potassium and phosphorus adsorbed on pumice were comparable in stem height, total leaf area, number of leaves and number of nodes to those grown in gravel containing a complete nutrient solution.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…6. Plants dependent upon magnesium, potassium and phosphorus adsorbed on pumice were comparable in stem height, total leaf area, number of leaves and number of nodes to those grown in gravel containing a complete nutrient solution.…”
Section: Discussionmentioning
confidence: 90%
“…At the elongation phase in the -K series, there was a relatively high potassium concentration in the plant with a corresponding low calcium content (4,5,6,8,15), a condition reflecting the high concentration of available potassium ions (tables IV and V). This calcium deficiency ( fig.…”
Section: Tissue Analysismentioning
confidence: 99%
“…Trials were conducted to improve the fertility of various soils by means of adding natural or synthetic ion exchangers containing one (Greenhill and Page, 1933;Wiklander, 1957) or several (Converse et al, 1943;Arnon and Grossenbacher, 1947;Doubsky et al, 1965;Podlesakova, 1979) nutrient ions. In some cases a positive effect of using such fertilizers was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of synthetic ion-exchange resins as a source of adsorbed ions for plant growth was first proposed by Schlenker (1942) and Converse et al, (1943) Their studies showed that in systems in which all nutrient ions were supplied in an adsorbed form, the high selectivity for Ca and Mg required daily additions of K to maintain adequate amounts of t h e s e ions in s o l u t i o n . In s t u d i e s of p l a n t response to nutrient ion concentration, control at realistic levels is imperative.…”
Section: Introductionmentioning
confidence: 99%